Pushing Peak Shapes to Perfection by High-Temperature Focus GC-IMS - Lukas Bodenbender; Sascha Rohn; Philipp Weller (Chemosensors)
Gas chromatography–ion mobility spectrometry (GC-IMS) is a powerful technique in the field of food and flavor analysis specifically, as well as for the determination of volatile organic compounds (VOCs) in general. It offers high sensitivity and selectivity, combined with a robust design. Sample preparation is typically not required, and operating principles under ambient conditions facilitate routine analysis and usage at points of care. As of now, a plethora of applications of GC-IMS exist in the fields of food analysis, primarily for determining flavors and evaluating the authenticity of food. However, the general issue of peak tailing has, so far, not been addressed in IMS. Typical drift tube applications (DTIMS) are designed with emphasis to high detection sensitivities and feature large void volumes. This study aimed to develop an optimized IMS instrument design (“focus IMS”) which allows for signal mapping of eluting compounds. Due to an optimized flow architecture of sample and drift gases, in combination with an increased drift tube temperature, peak tailing is decreased significantly. In this study, the influence of drift gas flow and IMS cell temperature on the peak shape of several relevant allergenic terpenes was investigated. The peak quality optimization of DTIMS approaches for especially high-boiling substances facilitates the analysis of complex matrices, such as cosmetics, Citrus peel, and essence oils, as well as terpenes and terpenoids in general.